TAFRO Syndrome in a Kidney Transplant Recipient That Was Diagnosed on Autopsy: A Case Report - Nagai, Marie; Uchida, Takahiro; Yamada, Muneharu; Komatsu, Shuuhei; Ota, Kohei; Mukae, Mitsuya; Iwamoto, Hitoshi; Hirano, Hiroshi; Karube, Miho; Kaname, Shinya; Oda, Takashi (Frontiers in Medicine, 2021)
A 57-year-old man who received a kidney transplant 4 years previously owing to unknown underlying disease presented with thrombocytopenia and fever. Hepatosplenomegaly and lymphadenopathy were observed, and development of prominent anasarca and worsening of renal function yielded the diagnosis of TAFRO syndrome. He was treated with high-dose steroids and plasmapheresis, and a thrombopoietin receptor agonist was administered for refractory thrombocytopenia. However, his general condition worsened, and he died on day 92. Histopathological analysis of a kidney autopsy specimen showed thrombotic microangiopathy characterized by glomerular endothelial swelling, mesangiolysis, and double contours of the glomerular capillary walls. His bone marrow showed megakaryocytic hyperplasia with mild reticulin fibrosis. Interestingly, these clinical and pathological features were remarkably similar to those the patient demonstrated before the kidney transplant, suggesting the recurrence of TAFRO syndrome. TAFRO syndrome is a rare systemic disorder whose concept has recently been established, but information on its long-term outcome is scarce. To our knowledge, this is the first case of TAFRO syndrome developing in a kidney transplant recipient, which suggests that disease recurrence occurs many years after the kidney transplant.